The effect of blended learning methods on diabetic foot care on knowledge and skills to prevent the risk of diabetic foot injuries in patients with type II diabetes mellitus in the work area of the Kapasa Health Center in Makassar City - Galandjindjinay, Amida; Wahyuni, Emmi; Thalib, Abdul; Mustafa, Sri Resky (CV. Paperhome Indonesia, 2024)
Background : Diabetes Mellitus is a chronic disease caused by genetic factors, which is characterized by a deficiency in insulin production by the pancreas and/or due to ineffective insulin production, thereby increasing the concentration of glucose in the blood, which in turn damages various body systems, because diabetics Mellitus is often not aware of this disease and only finds out about it when symptoms of the disease appear and complications begin. Methods : This type of research is quantitative with a pre-experimental type, one-group pretest-posttest with a total sample of 50 people using the Accidental Sampling technique. The pre-experimental research design uses a one-group pretest-posttest design approach, where this research will reveal the effect between variables by involving one group of subjects. Results : This study shows that the results of the paired t test show knowledge of diabetic foot care with a value of ρ-value = 0.000 (<α = 0.05), and skills of diabetic foot care with a value of ρ-value = 0.000 which means there is no effect of education health knowledge and skills of diabetic foot care in patients with type II diabetes mellitus. Conclusion : Efforts to provide education through the application of the blended learning method will increase the knowledge and skills of diabetic foot care to prevent the risk of diabetic foot injuries in type II DM sufferers. This research provides information for health workers (nurses), it is hoped that they will add information or literature, especially regarding the knowledge and skills of treating diabetic feet in patients with type II DM in caring for feet.